Walking the Americas : 1,800 miles, eight countries, and one incredible journey from Mexico to Colombia - Wood, Levison, 1982- (Atlantic Monthly Press, 2018)
"Starting in the Yucatán, Wood sets out on an epic walking voyage, moving through Belize, Guatemala, Honduras, Nicaragua, Costa Rica, and Panama, travelling in the opposite direction along vital migrant routes. Journeying from sleepy barrios to glamourous cities to Mayan ruins lying unexcavated in the wilderness, Wood forges new relationships along the way that stand at the heart of this book--and the personal histories, cultures, and popular legends he discovers paint a riveting history of Mexico and Central America. While contending with the region's natural obstacles, he partakes in family meals with local hosts, learns to build an emergency shelter, and witnesses the surreal beauty of the landscapes. Finally, Wood attempts to cross one of the world's most impenetrable borders: The Darién Gap from Panama into south America, a notorious smuggling passage and the wildest jungle he has ever navigated."--Jacket flap.